Nilai-Nilai Konseling Islam pada Syair Tari Saman di Kalangan Masyarakat Gayo - Lingga, Musdiansyah; Diana, Raden Rachmy (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2024)
This research aims to explore the Islamic counseling values contained in the Saman dance poetry and how these values are applied and lived by the Gayo community. The Saman dance, a cultural heritage of the Gayo community, is not only an artistic expression, but also reflects the Islamic counseling values that this community firmly holds. This study uses qualitative research methods with data collection techniques through in-depth interviews, participant observation, and text analysis of Saman dance poetry. The results of the research show that the Saman dance poetry consistently depicts Islamic values such as piety, morals and social values. The Gayo community applies these values as a guide for Islamic counseling in everyday life, strengthening social and spiritual ties within the community. By highlighting the relationship between traditional art and Islamic values, this research provides further insight into how art and culture can be an effective means of conveying Islamic counseling messages and strengthening moral values in local communities. The implications of these findings can help in the development of Islamic counseling programs that are integrated with cultural heritage in various communities.